2014
DOI: 10.3389/fpubh.2014.00159
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Psychosocial Correlates of After-School Activities among Chinese Adolescents in Hong Kong

Abstract: Using a cross-sectional design, this study (a) explores the prevalence of after-school activities among Chinese early adolescents and (b) assesses the relationships between participation in after-school activities, personal well-being, and family functioning. A total of 3,328 Grade 7 students (mean age = 12.59 years, SD = 0.74) completed a self-administered questionnaire. Results showed that the majority of adolescents returned home under adult supervision. Further analyses showed the associations between afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 62 publications
2
5
0
Order By: Relevance
“…Family conflicts are linked to adolescent self-harm and suicidal behaviors, and the effect can be long-lasting. 45 In addition to conflicts, family communication also contributed to the difference between wave 1 and wave 6 suicidal behavior. However, the decline rate for suicidal behavior among adolescents with weaker family communication was faster.…”
Section: Family Functioning and Self-harm Or Suicidal Behaviormentioning
confidence: 99%
“…Family conflicts are linked to adolescent self-harm and suicidal behaviors, and the effect can be long-lasting. 45 In addition to conflicts, family communication also contributed to the difference between wave 1 and wave 6 suicidal behavior. However, the decline rate for suicidal behavior among adolescents with weaker family communication was faster.…”
Section: Family Functioning and Self-harm Or Suicidal Behaviormentioning
confidence: 99%
“…In a study among 3,328 Grade 7 students by Ma and Shek (2014) titled "prevalence and psychosocial correlates of after-school activities among Chinese adolescent in Hong Kong", it was reported that involvement in extra-curricular activities promoted positive youth development qualities, life satisfaction, positive adjustment, and social interaction. The implication of this is that the enhancement of positive developmental qualities, competence and social interaction is a good ground for the development of positive social self-efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, positive attributes of adolescents were assessed via the 80-item Chinese Positive Youth Development Scale (CPYDS) [ 59 , 60 ]. The positive attributes are categorized into fifteen dimensions including healthy relationship with adults, psychosocial competencies, moral competence, self-determination, etc.…”
Section: Methodsmentioning
confidence: 99%